Handbook of narrative analysis - Herman, Luc; Vervaeck, Bart (Frontiers of narrative, 2019)
"Handbook of Narrative Analysis is the go-to book for understanding and interpreting narrative. Luc Herman and Bart Vervaeck have revised and extended the first edition by describing and applying the last fifteen years of cutting-edge scholarship in the field of narrative theory"- Resumé vydavatel